Enhanced electrochemical performances of LiNi0.5Mn1.5O4 by surface modification with Cu nanoparticles - Zhao G.; Lin Y.; Zhu W.; Yang W.; Huang Z. (Journal of Mining and Metallurgy. Section B: Metallurgy)
5V spinel LiNi0.5Mn1.5O4 cathode is prepared by traditional solid-state method and nano-Cu particles were derived from a chemical reduction process. The effect of Cu-coating on the electrochemical performances of LiNi0.5Mn1.5O4 cells, in a wide operation temperature range (-10°C, 25°C, 60°C), is investigated systematically by the charge/discharge testing, cyclic voltammograms and impedance spectroscopy, respectively. The results demonstrate that the modified material exhibits remarkably enhanced electrochemical reversibility and stability. Cu-coated material has much lower surface and charge transfer resistances and shows a higher lithium diffusion rate. The Cu coating layer as a highly efficient lithium ion conductor, acted as a highly efficient protector to restrain the contact loss.